Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1021/ed076p349
|View full text |Cite
|
Sign up to set email alerts
|

Nucleogenesis! A Game with Natural Rules for Teaching Nuclear Synthesis and Decay

Abstract: Nucleogenesis! is a simple and engaging game designed to introduce undergraduate physics or chemistry students to nuclear synthesis and decay by simulation of these processes. By playing the game, students become more familiar with nuclear reactions and the "geography" of the table of isotopes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…5 Studies have indicated that card and board games dealing with chemistry topics are successful in teaching chemistry, 8−11 capturing interest, developing collaborative skills, 12 providing motivation, 12,13 and addressing visual learning styles 14 as well as decreasing the anxiety and apprehensions of students and teachers. 15,16 To date, many games have been developed to review and reinforce a variety of chemistry topics, such as the nomenclature, symbols and formulas of chemical species, 10,15,17,18 the families of chemical elements, 13 the electronic structures of atoms, 19 the periodic table, 8 the formation of compounds, 10,18,20 reaction rate theory, 21 nuclear synthesis, 22 stoichiometry, 23 crystallography, 24 and organic chemistry. 1,12,25,26 These games are mostly focused on specific subjects in chemistry.…”
Section: ■ Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Studies have indicated that card and board games dealing with chemistry topics are successful in teaching chemistry, 8−11 capturing interest, developing collaborative skills, 12 providing motivation, 12,13 and addressing visual learning styles 14 as well as decreasing the anxiety and apprehensions of students and teachers. 15,16 To date, many games have been developed to review and reinforce a variety of chemistry topics, such as the nomenclature, symbols and formulas of chemical species, 10,15,17,18 the families of chemical elements, 13 the electronic structures of atoms, 19 the periodic table, 8 the formation of compounds, 10,18,20 reaction rate theory, 21 nuclear synthesis, 22 stoichiometry, 23 crystallography, 24 and organic chemistry. 1,12,25,26 These games are mostly focused on specific subjects in chemistry.…”
Section: ■ Backgroundmentioning
confidence: 99%
“…To date, many games have been developed to review and reinforce a variety of chemistry topics, such as the nomenclature, symbols and formulas of chemical species, ,,, the families of chemical elements, the electronic structures of atoms, the periodic table, the formation of compounds, ,, reaction rate theory, nuclear synthesis, stoichiometry, crystallography, and organic chemistry. ,,, These games are mostly focused on specific subjects in chemistry. In this activity, a comprehensive set of three games (Elemental Periodica, Groupica, Compoundica) is presented, encompassing many interrelated subjects and concepts: names, symbols, atomic numbers and properties of the elements, the placement of the elements on the periodic table, examples of everyday objects in which the elements are found, the properties of the groups (e.g., s and p blocks) on the periodic table, and the formation of compounds from the elemental ions.…”
Section: Introductionmentioning
confidence: 99%
“…One was to reorder the topics to thread a history of our material world from nucleogenesis to anthropic perturbations, a progression that had been appreciated in my environmental chemistry course. The other change was to flip the classroom for active learning, primarily by creating a comprehensive set of ''ConcepTests'' with which to implement Eric Mazur's Peer Instruction method across all topics, 43 but also by developing games with natural rules 44,45 and drawing exercises focused on central concepts and details of apparati. Teaching innovations were well received and I hope to find time in retirement to broaden access to relevant materials.…”
Section: Teachingmentioning
confidence: 99%
“…However, nuclear chemistry and radioactivity can be difficult subjects to teach due to the existing misconceptions about these topics and the lack of available hands-on activities for aiding in their instruction. The development of these types of activities or laboratory experiments that are amenable to the K–12 and undergraduate levels is challenging due to the general concern at both the institutional and societal levels regarding handling radioactive materials. Despite these challenges, there have been significant efforts in designing new K–12 activities and undergraduate-level laboratory experiments that enhance student understanding and dispel misconceptions regarding nuclear chemistry.…”
Section: Introductionmentioning
confidence: 99%